Perfil epidemiológico e biologia tumoral do câncer de mama em mulheres da Região Norte do Brasil - Franca, Daniele Carvalhais [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
INTRODUCTION: Retrospective cohort to describe the epidemiological data of women with breast cancer at a referral center in oncology in the North region of Brazil between January 2012 and December 2021. RESULTS: 420 patients were included, most of them female (99.5%), with complete elementary school (33.3%) and brown (68%). The mean age at diagnosis was 49 years. Most patients are from Rondônia (87.8%). Forty-five percent were born in the North region and 55% in other regions of Brazil. Eighty percent of injuries were classified as CDI. Regarding molecular subtypes, 32.7% were luminal A, 25.1% luminal B, 19.4% HER2 overexpressed and 12.8% triple negative. 76.8% of patients received chemotherapy; radiotherapy, 81.5%; 91.2% underwent surgery; 71.8% received hormone therapy and 21.2% targeted therapy. When the patients were subdivided by age £40 years and > 40 years, there was a statistically significant difference in the association with staging (p=0.000), histological type (p= 0.035), molecular subtype (p=0.000), neoadjuvant chemotherapy (p=0.000). = 0.005) and genetic counseling (p=0.001). There was a statistically significant correlation with color/race (p= 0.012), staging (p= 0.005), family history of any type of cancer (p= 0.040), molecular subtype (p= 0.001), neoadjuvant chemotherapy (p=0.000) and radiotherapy (p= 0.000). The median survival was 7.99 years. The 5-year overall survival was 81%. Survival in relation to staging was lower the higher the stage. Twenty-four distinct variants were described in patients undergoing genetic testing, 16 of uncertain significance (VUS) and 8 pathogenic. Three new variants have been described: ATM (c.8726G>C), BRCA2 (c.2232A>C) and ERCC5 (c.2164G>Ap). CONCLUSION: In this study, the age at diagnosis of breast cancer was lower, the tumors are of a more aggressive subtype and patients are admitted in more advanced stages. Approximately 46% of patients did not start treatment within the established period. This rate is better compared to national data in which 50.9% of women are in this situation. Survival is lower compared to national and international data. Despite the small number of patients referred for genetic testing, it is important to search for germline mutations in this population.

INTRODUÇÃO: Coorte retrospectiva com objetivo de descrever os dados epidemiológicos referentes às mulheres com diagnóstico de câncer de mama atendidas em centro de referência em oncologia na região Norte do Brasil entre janeiro de 2012 e dezembro de 2021. RESULTADOS: Foram incluídos 420 pacientes, a maioria do sexo feminino (99,5%), com primeiro grau completo (33,3%) e pardas (68%). A média de idade ao diagnóstico foi de 49 anos. A maioria das pacientes são procedentes de Rondônia (87,8%). Quarenta e cinco por cento nasceram na região Norte e 55% em outras regiões do Brasil. Oitenta por cento das lesões foram classificadas como CDI. Em relação aos subtipos moleculares, 32,7% foram luminais A, 25,1% luminais B, 19,4% HER2 superexpresso e 12,8%, triplo negativos. Receberam quimioterapia 76,8% das pacientes; radioterapia, 81,5%; 91,2% foram submetidas a cirurgia; 71,8% receberam hormonioterapia e 21,2%, terapia alvo. Ao subdividir as pacientes por idade £40 anos e > 40 anos, houve diferença estatisticamente significante na associação com estadiamento (p=0,000), tipo histológico (p= 0,035), subtipo molecular (p=0,000), realização de quimioterapia neoadjuvante (p= 0,005) e aconselhamento genético (p=0,001). Houve correlação estatisticamente significante com cor/raça (p= 0,012), estadiamento (p= 0,005), histórico familiar para qualquer tipo de câncer (p= 0,040), subtipo molecular (p= 0,001), quimioterapia neoadjuvante (p=0,000) e radioterapia (p= 0,000). A mediana de sobrevida foi de 7,99 anos. A sobrevida global em 5 anos foi 81%. A sobrevida em relação ao estadiamento foi menor quanto mais alto o estágio. Foram descritas 24 variantes distintas nas pacientes submetidas a teste genético, 16 de significado incerto (VUS) e 8, patogênicas. Foram descritas três novas variantes: ATM (c.8726G>C), BRCA2 (c.2232A>C) e ERCC5 (c.2164G>Ap). CONCLUSÃO: Neste trabalho, a idade ao diagnóstico do câncer de mama foi menor, os tumores são de subtipo mais agressivo e as pacientes são admitidas em estágios mais avançados. Aproximadamente 46% das pacientes não começaram a tratar no prazo estabelecido. Essa taxa é melhor em comparação com dados nacionais em que 50,9% das mulheres se encontram nessa situação. A sobrevida é menor em comparação com dados nacionais e internacionais. Apesar do pequeno número de pacientes encaminhadas para o teste genético, é importante a pesquisa de mutações germinativas nessa população.
Epidemiological profile of breast cancer in a reference center in the north region of Brazil
Keywords: Câncer de mama; Amazônia; Região norte; Brasil